Information Systems UI/UX Design of Online Tickets for Situ Pasir Maung Tourism in Dago Village Using the Figma Application - Hidayanti, Putri Eka; Handayani, Rani Irma; Rifai , Bakhtiar (Politeknik Ganesha Medan, 2023)
has several interesting tours, one of which is Situ Pasir Maung, a place in the form of a natural tourism park located in Dago Village, Parung Panjang District, Bogor Regency. However, ticket purchases can only be made by buying directly on the spot when entering the tourist spot. This can make it difficult to order tickets due to the large number of visitors. So here a design for an e-ticket application will be made using the design thinking method to analyze and design a mobile application for online ticket ordering at Dago Tourism. In this design the editing software used is Figma, and in this study will only make UI/UX designs related to online ticket purchases. UI/UX design of the Design Thinking method for Situ Pasir. The Maung tourist ticket application was created and a prototype of the application was tested by sending a questionnaire to 20 respondents with an average score of 4.021 and most of the responses from potential users said that the tour ticket prototype was easy to understand and use. So here we will try to make an e-ticket application design. E-tickets can make it easier for buyers or visitors to get them because there is no need to come directly to tourist attractions. Ticket purchases can be made through easy-to-use online ordering